Does Systemic Methotrexate Therapy Induce Azole Resistance among Endogenous Candida Strains? - Dawid Żyrek; Joanna Nowicka; Magdalena Pajączkowska; Ewa Morgiel (MDPI AG, 2021)
Background: Research confirms that Candida spp. incubated with methotrexate develop multi-drug resistance to azoles, but it is not clear whether this phenomenon occurs in vivo in patients treated with cytostatics. The aim of the study was to assess whether systemic methotrexate therapy induces resistance to azoles among endogenous Candida strains in patients with rheumatological diseases. Methods: The test group consisted of 52 rheumatological patients on methotrexate therapy, who have never been exposed to fluconazole. The control group was composed of 49 individuals who have never been exposed to either methotrexate or fluconazole. Oral swab and clinical information were obtained from each participant. The acquired material was cultured, then each strain was isolated and identified (MALDI TOF). Subsequently, minimal inhibitory concentration (MIC) for fluconazole was determined. Results: MIC values ranged from <0.125 to 64 µg/mL with the most common result <0.125 µg/mL. Samples obtained from 4 patients of the test group and 2 patients of the control group contained strains resistant to fluconazole. Conclusions: Despite slightly higher incidence of fluconazole-resistant strains among patients on systemic methotrexate therapy, we found no solid evidence to support the hypothesis that methotrexate induces resistance to azoles among endogenous Candida strains in patients with rheumatological diseases.